Discover Your Spiritual Type - Ware, Corinne (Rowman & Littlefield Publishers, 1995)
From Urban T. Holmes's spiritual typology and her own experience as a spiritual director and pastoral counselor, Ware provides a framework for people to name and understand their spiritual experience-in much the same way the Myers-Briggs typology provides a framework for understanding personality types. Readers explore four spiritual types--head, heart, mystic, and Kingdom--and exercises allow individuals and groups to assess their type. Additional information for clergy to use this tool with congregations is included, which will help them gain greater understanding of how members learn about, worship, and celebrate God--and why there may be tension about such issues as the form or content of the worship service.